1998
DOI: 10.1001/archotol.124.11.1239
|View full text |Cite
|
Sign up to set email alerts
|

Pilomatrixoma of the Head and Neck in Children

Abstract: Pilomatrixoma is a rare, benign skin tumor, but practitioners should be aware of its clinical features. Diagnosis is usually easy based on clinical findings, but computed tomographic scan is helpful, especially in cases involving tumors located in the parotid region. Spontaneous regression is never observed. Complete surgical excision, including the overlying skin, is the treatment of choice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(46 citation statements)
references
References 12 publications
1
44
1
Order By: Relevance
“…[1] In France, a retrospective study in one surgery clinic revealed 33 patients who had surgery for pilomatrixoma between 1989 and 1997. [2]…”
Section: Introductionmentioning
confidence: 99%
“…[1] In France, a retrospective study in one surgery clinic revealed 33 patients who had surgery for pilomatrixoma between 1989 and 1997. [2]…”
Section: Introductionmentioning
confidence: 99%
“…Duflo et al . [11] noticed maximum tumor size of 3 cm diameter, we observed 1.6 cm as the mean tumor size.…”
Section: Discussionmentioning
confidence: 49%
“…3 There is a female pre-ponderance for the affection of the disease. 4,5 The most common site of affection is head and neck area with more than half the reported cases in this area. The most common site to be affected in the head and neck are frontal, temporal, peri-orbital and pre-auricular.…”
Section: Discussionmentioning
confidence: 99%